Spooky Interaction at a Distance in Cave and Surface Dwelling Electric Fishes - Fortune, Eric S.; Andanar, Nicole; Madhav, Manu; Jayakumar, Ravikrishnan P.; Cowan, Noah J.; Bichuette, Maria Elina; Soares, Daphne (Frontiers in Integrative Neuroscience, 2020)
Glass knifefish (Eigenmannia) are a group of weakly electric fishes found throughout the Amazon basin. We made recordings of the electric fields of two populations of freely behaving Eigenmannia in their natural habitats: a troglobitic population of blind cavefish (Eigenmannia vicentespelaea) and a nearby epigean (surface) population (Eigenmannia trilineata). These recordings were made using a grid of electrodes to determine the movements of individual fish in relation to their electrosensory behaviors. The strengths of electric discharges in cavefish were larger than in surface fish, which may be a correlate of increased reliance on electrosensory perception and larger size. Both movement and social signals were found to affect the electrosensory signaling of individual Eigenmannia. Surface fish were recorded while feeding at night and did not show evidence of territoriality. In contrast, cavefish appeared to maintain territories. Surprisingly, we routinely found both surface and cavefish with sustained differences in electric field frequencies that were below 10 Hz despite being within close proximity of less than one meter. A half century of analysis of electrosocial interactions in laboratory tanks suggest that these small differences in electric field frequencies should have triggered the jamming avoidance response. Fish also showed significant interactions between their electric field frequencies and relative movements at large distances, over 1.5 meters, and at high differences in frequencies, often greater than 50 Hz. These interactions are likely envelope responses in which fish alter their EOD frequency in relation to changes in the depth of modulation of electrosocial signals.